The fundamental principles of CMF design colour, material, finish - Becerra, Liliana (Amsterdam, The Netherlands Frame Publishers, 2016)
"Introducing the CMF process and detailing the areas of colour, finish and material design, this book serves as a valuable source of information about this emerging professional discipline and its fundamental principles -- back cover
Introduction to CMF design -- Emotional context -- Functional context -- CMF creation -- Functional attributes of colours -- Culture and context of colours -- Materials first -- Material design based on sustainability -- Material design based on manufacturing process -- Surface design based on product strategy -- Sensorial finishes -- Functional finishes.
Prof. Jocelyn C. Pinzon (Recommending faculty) - Bookfair2017
Includes bibliographical references (pages 206-207)
Keywords: Product design; Color in design; Finishes and finishing